2000
DOI: 10.1148/radiology.217.2.r00oc23421
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Mapping of Intraabdominal Adhesions by Using Functional Cine MR Imaging: Preliminary Results

Abstract: Detection of visceral slide at functional cine MR imaging is easy to perform and represents a well-tolerated and accurate procedure for use in the identification of intraabdominal adhesions in patients with chronic pain and equivocal clinical findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 14 publications
1
59
1
2
Order By: Relevance
“…In general, the results published by Lienemann et al [10] in 2000 were confirmed and indications for this easy-toperform and well-tolerated examination technique include the clinical confirmation of intraabdominal adhesions in patients with known history of adhesions or with chronic abdominal pain without any signs of obstruction or ischemia. In addition, our study provides MR results of a larger patient cohort compared with the initial study by Lienemann and co-workers.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…In general, the results published by Lienemann et al [10] in 2000 were confirmed and indications for this easy-toperform and well-tolerated examination technique include the clinical confirmation of intraabdominal adhesions in patients with known history of adhesions or with chronic abdominal pain without any signs of obstruction or ischemia. In addition, our study provides MR results of a larger patient cohort compared with the initial study by Lienemann and co-workers.…”
Section: Resultsmentioning
confidence: 71%
“…In our study, a section-by-section functional cine MRI for the depiction of visceral slide throughout the entire abdomen, which was first introduced by Lienemann et al [10], was used. As criteria for the detection of intraabdominal adhesions, the absence of movement or separation of adjacent structures were employed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Οι συγγραφείς βρήκαν μία συνολική ευαισθησία της μεθόδου 88% και ειδικότητα 93% [163] . Ένα χρόνο μετά, οι Katayama και συνεργάτες, αξιολόγησαν μετεγχειρητικές συμφύσεις στην πύελο σε 52 γυναίκες που είχαν υποβληθεί σε γυναικολογικές επεμβάσεις.…”
Section: διακοιλιακο υπερηχογραφημαunclassified